Współpraca transgraniczna w zakresie dochodzenia publicznych należności pieniężnych - Klat-Wertelecka, Lidia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Co-operation between the authorities in the pursuit of public-law claims is a thing of great significance to border areas. The essence of that co-operation is for Polish public-administration authorities to give legal assistance to foreign authorities and to receive such assistance from foreign authorities; the legal basis is found in the Council Directive 2010/24/EU of 16 March 2010 concerning mutual assistance for the recovery of claims relating to taxes, duties and other measures (OJ L 84/1) and in the Polish Act of 11 October 2013 on the Mutual Assistance for the Recovery of Taxes, Customs Duties and Other Financial Debts (Polish Journal of Laws: Dz. U. 2013.1289 as amended). The purpose of the co-operation model adopted among EU member states is to better safeguard the financial interests of the member states whilst ensuring the proper functioning of the single market. At the same time, the autonomy of the national rules set out in the implementing legislation is preserved with regard to the means and measures and the procedure involved in the recovery of pecuniary debts of public-law origin.
Keywords: legal assistance; administrative enforcement; executory entitlement; public-law claims; co-operation